2018
DOI: 10.3390/s18030706
|View full text |Cite
|
Sign up to set email alerts
|

An Affordable Insole-Sensor-Based Trans-Femoral Prosthesis for Normal Gait

Abstract: This paper proposes a novel and an affordable lower limb prosthesis to enable normal gait kinematics for trans-femoral amputees. The paper details the design of a passive prosthesis with magneto-rheological (MR) damping system and electronic control. A new control approach based on plantar insole feedback was employed here. Strategically placed sensors on the plantar insole provide required information about gait cycle to a finite state controller for suitable action. A proportional integral (PI) based current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…For patients whose lower limb movement chain is damaged due to limb loss, prosthesis is needed to make up the missing lower limb parts and functions, promote physical activities, and make lower limb activities tend to be normal. [69][70][71] Li et al 72 designed an asymmetric exoskeleton, as shown in Figure 17, the left leg is an exoskeleton mechanical leg worn on the healthy leg of the amputees. The right leg is an assisted lower limb prosthesis composed of intelligent lower limb prosthesis and exoskeleton mechanical leg, which is connected to the stump of the disabled thigh through the prosthetic receiving cavity.…”
Section: Daily Life Assistive Robot (Dlar)mentioning
confidence: 99%
“…For patients whose lower limb movement chain is damaged due to limb loss, prosthesis is needed to make up the missing lower limb parts and functions, promote physical activities, and make lower limb activities tend to be normal. [69][70][71] Li et al 72 designed an asymmetric exoskeleton, as shown in Figure 17, the left leg is an exoskeleton mechanical leg worn on the healthy leg of the amputees. The right leg is an assisted lower limb prosthesis composed of intelligent lower limb prosthesis and exoskeleton mechanical leg, which is connected to the stump of the disabled thigh through the prosthetic receiving cavity.…”
Section: Daily Life Assistive Robot (Dlar)mentioning
confidence: 99%
“…Therefore, in view of the various problems in practical applications, many scholars have proposed different improvements and optimization methods based on traditional structures, which has greatly enhanced the performance of the MRF based devices. Furthermore, different from the above application types, the MRF has been further developed, and has in recent years become an important part of the haptic feedback system (Song et al, 2018b) and artificial limbs (Pandit et al, 2018) in the medical field. In the haptic feedback system based on the MRF, using the controlled rheological characteristics, a resistance environment similar to the real sense of touch is generated and transmitted to the operator, which is widely applied to the teleoperated catheter operating system (Song et al, 2018a) or intelligent haptic interface devices (Topcu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, joint kinematics may be estimated using both inertial sensors [32] or optical fiber [33]. Instrumented insoles may also be used, including for controlling lower-limbs prosthesis [34]. The method to provide such estimate robustly is yet to be developed.…”
Section: Discussionmentioning
confidence: 99%